Competitiveness of profit-loss-sharing mode of financing using constant market share competitiveness index - Abdul Jalil, Mohd Aisha Nuddin; Ibrahim, Noor Akma (Academic Inspired Network, 2019)
A systematic method is needed in understanding and measuring the progress in the development of Islamic financial instruments. This paper addresses the issue of the competitiveness of profit-loss-sharing (PLS) instruments relative to the conventional instruments in a country. The widely employed descriptive Constant Market Share (CMS) analysis tools normally used in analysing the competitiveness of exports of a country is proposed to be used in this case. As the identities used in CMS analysis are general mathematical identities originated from the product rule for the differentiation of the product of two functions and relate to changes in shares of entities out of the total share in discrete cases, thus it can be explored to be used for other fields other than the change in exports. However, CMS analysis measurement is prone to a number of methodological shortcomings which stem from the CMS identities used in the analysis. Namely, the discrete approximation of continuously changing trade patterns, the interaction effects residual from the CMS identities decomposition and the arbitrary choice of weights attached to base periods. Aisha Nuddin et al., (2018) introduced a net-share approach index and geometric framework to address some of the shortcomings of the classic CMS analysis approach. This paper demonstrated how the CMS net-share approach index can be used in analysing the competitiveness of different modes of investment instruments in a country. As an example, an application of this method in analysing the performance of PLS mode of financing in Malaysia in year 2015 is presented at the end of the paper.